Antibody Testing for Neurological Autoimmune Disorders: Evaluation of Best Practices at a Tertiary Referral Center - Fredrich, Sarah E.; Vernino, Steven; Blackburn, Kyle M. (Frontiers in Neurology, 2021)
Background: Autoimmune neurology is a rapidly evolving field of study, where best practices for neurological antibody testing have yet to be determined. The growing number of options for antibody panel testing can create confusion amongst ordering clinicians and lead to ordering several concurrent panels (i.e., overlapping evaluations) or repeat panel evaluations. This study determined the frequency of these evaluations for autoimmune and paraneoplastic disorders and investigated how these practices informed clinical decision making and management. Methods: This was a retrospective observational study of adult patients presenting to University of Texas Southwestern (UTSW) in 2017 with requests for antibody panels for autoimmune encephalitis and paraneoplastic disorders. Individuals with more than one panel requested were defined as either an overlapping evaluation (more than one panel requested within 14 days) or repeat evaluation (more than one panel requested 14 or more days apart). For those individuals with repeat panel testing, the proportion of panels with a change in antibody status or subsequent changes in clinical diagnosis and decision making were recorded. Results: There was a total of 813 panels sent on 626 individuals. Twenty percent (126 individuals) had more than one panel requested. Only 10% of individuals had a matched serum and CSF evaluation. Forty-seven overlapping evaluations were performed in 46 (7.3%) of the individuals studied. Fifty-four (8.6%) individuals underwent 70 repeat evaluations encompassing 79 panels (9.7% of total panels ordered). Ten repeat evaluations showed a change in antibody status, of which only two were clinically significant. There was a single case where clinical management was affected by repeat autoantibody evaluation. Conclusions: Ordering practices for suspected autoimmune encephalitis and paraneoplastic disorders are suboptimal with frequent overlapping antibody panel evaluations and non-paired serum/CSF samples at our center. Repeat autoantibody testing is a commonplace practice yet yielded novel information in only a minority of cases. These new results were, as a rule, clinically irrelevant and changed clinical decision making in <1% of cases. There is limited utility in these practice patterns. Future efforts should be directed at the development and standardization of neurological autoimmune and paraneoplastic autoantibody testing practice standards.